FATWA INSTITUTIONS IN ISLAMIC LAW - Setyaningsih (Awang Long Law Review, 2022)
Fatwa is one of the products of Islamic legal thinking in the form of ijtihad of scholars who formulate a formula for legal provisions in response to questions raised regarding various aspects of law. The fatwafatwas of the Ulama have a casuistic nature and tend to be dynamic regarding problems in society that are important to know about the legal provisions of the Islamic community. These fatwafatwas are contributions to the development of Islamic law in particular and national law in general.